2001
DOI: 10.1521/suli.31.2.153.21511
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrative Model of Suicide Attempt: A Cognitive Psychological Approach

Abstract: Applying a cognitive approach, the purpose of the present study was to expand previous research on stress-vulnerability models of depression and problem-solving deficits, as it relates to suicide attempt. Structural equation modelling, involving latent variables, was used to evaluate (a) whether low self-esteem, a low sense of self-efficacy, loneliness, and divorce constituted vulnerability factors for the development of depression; (b) whether hopelessness and suicidal ideation mediated the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
80
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 73 publications
(126 reference statements)
8
80
0
4
Order By: Relevance
“…This increased predictive power is likely due to the inclusion of complementary information from multiple variables and to the more complex functional form of these models. This finding is in agreement with previously published studies that show that risk factors can modify each other's effects (15,13,(26)(27)(28)(29)(30)(31), and supports the need for complex theoretical models of suicidal behavior (22) that include multiple factors that mediate and moderate each other's effect.…”
Section: Discussionsupporting
confidence: 92%
“…This increased predictive power is likely due to the inclusion of complementary information from multiple variables and to the more complex functional form of these models. This finding is in agreement with previously published studies that show that risk factors can modify each other's effects (15,13,(26)(27)(28)(29)(30)(31), and supports the need for complex theoretical models of suicidal behavior (22) that include multiple factors that mediate and moderate each other's effect.…”
Section: Discussionsupporting
confidence: 92%
“…Our results may have clinical implications for working with suicidal individuals, in general, but particularly for African-American, female attempters. It may be assumed that suicide attempters are already at a disadvantage with regard to coping, as they often have poor problem-solving, interpersonal and emotion regulation skills (Dieserud, Roysamb, Ekeberg, & Kraft, 2001;Pollock & Williams, 2001). Our results indicate that, for our sample of African-American suicide attempters, perhaps a lack of spiritual well-being contributes to vulnerability to the demands of everyday life.…”
mentioning
confidence: 69%
“…Rather, these studies found that the relationship is mediated by suicidal ideation. That is, suicidal ideation is influenced by level of hopelessness and suicidal ideation influences risk of suicide attempt (Valtonen et al, 2005;Sokero et al, 2003;Dieserud et al, 2001). However, it is important to note that literature in this area has been inconsistent.…”
Section: Discussionmentioning
confidence: 99%